Padronização da genotipagem de alelos dos sistemas de grupo sanguíneo Diego, Dombrock e Duffy por PRC em tempo real na Fundação Hemominas - Adão Rogério da Silva (2018)
The determination of red blood cell antigens for the most relevant blood group systems like ABO, Rh, and Kell is commonly performed in blood banks. However, in the last decade, cases of hemolytic transfusion reactions caused by antibodies related to blood group antigens not routinely evaluated in pre-transfusion tests have been reported. These reports includesystems like Diego e Dombrock. The determination of antigens and antibodies related to these systems is hampered by the paucity of appropriate reagents for serologic typing. Thus, molecular biology techniques become a valuable tool in immunohematology laboratories, since they allow inference of the phenotype from the genetic analysis. The present study aimed to standardize the genotyping of variants of the Duffy (FY*A, FY*B and FY*BES), Diego (DI*A and DI*B) and Dombrock (HY) blood group systems using real-time PCR. Results indicate that there was complete agreement between the results of PCR-RFLP (techniques described in the literature) and the real time PCR assays standardized in this study. The reproducibility and repeatability of the tests was measured by calculation of thecoefficient of variation for cycle threshold from triplicate samples. The mean values of the coefficients of variation did not exceed 5.6%. The limit of detection was found to be 1 ng of DNA per reaction for DI*A/DI*B and 100 pg for HY. These limits are compatible with the DNA concentrations usually employed in molecular biology laboratories. These results demonstrate that the standardized techniques present potential for routine use in blood banksand may be useful in screening of blood donors with rare phenotypes.